RECOVERY ENZIM KATEPSIN DARI LIMBAH CAIR SURIMI - Tati Nurhayati; Hani Novanti; Agoes M Jacoeb (UII, 2015)
Surimi processing waste liquid that still contains high sarcoplasmic proteins that can still be used, one of which is an cathepsin enzyme. The purpose of the study was to determine the parameters of pH and temperature in recovery of enzyme cathepsin from surimi wastewater. The results showed that the best recovery of cathepsin enzyme is obtained at pre-treated pH 5 and heating at a temperature of 60 °C. In these conditions, cathepsin enzyme has a specific activity 17.90 U / mg and a multiple of 117 times the purity of surimi wash water. Keywords: cathepsin, enzyme recovery, pH, surimi wastewater, temperature